THE ROLE OF THE SCHOOL PROFESSIONAL COUNSELOR IN THE VOCATIONAL ORIENTATION SYSTEM - PIETRUK, Witold (Trends in education, 2013)
The article shows the results of the survey conducted among the third class students attend to junior high schools in Brzeg district (Opole province). The aim of the research was the diagnosis if the professional counselor is needed in junior high schools. There is also shown a role of him in the vocational orientation system, as well as the scale of youth interest of his job and his attitude to planning the youth's educational and vocational path.
Keywords: A student of junior high school; a school professional counselor; demand for advisory services